MUSLIM COMMUNITY IN GERMANY: CURRENT CHALLENGES AND OPPORTUNITIES - Meirison Meirison; Darni Yusna (Universitas Islam Negeri Imam Bonjol Padang, 2021)
A recent study showed that the number of Muslims had increased significantly in Germany since 2015. Many of them still face challenges in terms of employment and training. Religion may be a secondary cause of these challenges,